Validating the measuring instrument for determinants of guest perceived value in peer-to-peer accommodation in Malaysia: a pilot study - Izyanti Awang Razli; Salamiah A. Jamal; Mohd Salehuddin Mohd Zahari (Human Resource Management Academic Research Society (HRMARS), 2018)
Numerous studies on guest perceived value has been done in different field which leads to guest satisfaction and guest behavioral intention in an organization. However, far too little attention has been paid on study of guest perceived value specifically on peer to peer accommodation industry in Malaysia. Therefore, by using quantitative approach, the purpose of this pilot study is to assess the validity and reliability of the instrument used in measuring the determinant of guest perceived value in peer to peer accommodation which may affect the future behavioral intentions of guest to revisit such non-traditional accommodation type. A 35-sample data were analysed using the statistical software SPSS version 22. Prior to that, a content and face validity, reliability and data normality were examined based on expert assessment. The result shows that the measuring instruments used in this study are reliable and the data is proved of rational normality. The findings of this study provided overall support for the proposed measuring instrument for further research.